Application of screening tools for environmental hazard and risk to support assessment and subsequent prioritization of effluent discharges from the oil and gas industry. (23rd March 2021) - Worden, Joy R.; Di Paolo, Carolina; Whale, Graham F.; Eadsforth, Charles V.; Michie, Eleanor; Lindgren, Avila; Smit, Mathijs G.D.
Abstract: Assessment and management of effluent discharges are key to avoiding environmental deterioration. Often compliance with discharge regulations and permits is based on a limited set of chemical parameters, while information on whole effluent hazardous properties (toxicity, bioaccumulation potential, persistence) and environmental risks is lacking. The need to collect those data and to become more effective in quickly identifying high‐risk activities, without extensive laboratory testing, has led to the development of screening tools to complement information on chemical composition. A simple, Tier 1 screening "toolbox" is proposed which is comprised of solid‐phase microextraction with gas chromatographic (SPME‐GC) analysis, the in‐vitro ecotoxicity assay Microtox, and a simple weathering assay. When combined with dilution modeling, screening‐level risk assessments can be performed, providing additional lines of evidence to support a weight of evidence type of analysis. Application of the toolbox enables prioritization of discharges that may be deemed to require higher tier assessment. The toolbox was trialed on a number of produced water samples collected from offshore oil and gas facilities and effluents from petroleum processing and manufacturing sites. In contrast to what has been reported for petroleum products, results showed only moderate correlation between bioavailable hydrocarbons (bHCs) and toxicity, which might be related to the possible presence of toxic contaminants from other chemical classes or to methodological issues such as suboptimal conditions during transport. The methods employed were quick, inexpensive, and simple to conduct. They require relatively small volumes of sample, which is especially advantageous when evaluating discharges from remote offshore facilities. The toolbox adds valuable information on whole effluent properties to existing data, for example, on chemical composition, which can improve understanding of which discharges are more likely to pose a risk to the environment and so require further investigation or risk management. Integr Environ Assess Manag 2021;17:1025–1036. © 2021 Shell International B.V. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC) KEY POINTS: A simple screening "toolbox, " consisting of solid‐phase microextraction with gas chromatographic (SPME‐GC) analysis, Microtox, and a weathering assay, has been developed to assess ecotoxicity, bioaccumulation potential, and persistence of oil and gas industry effluents, which supports the assessment of potential environmental risk of effluent discharges. The screening assays are quick, inexpensive, and straightforward to conduct in the laboratory, requiring relatively small sample volumes, which is particularly advantageous when evaluating discharges from remote locations. A trial study on produced water discharges and effluents from manufacturing sites demonstrated the value of the whole effluent screening data for the prioritization of discharges that may be deemed to require higher tier assessment. The screening toolbox is proposed as Tier 1 of an overall 4‐tiered discharge assessment strategy for global facilities within the oil and gas industry.